Effect of controlling on the economic performance of smes in the Czech Republic - Kruml, Lukáš; Duspiva, Pavel (Univerzita Pardubice, 2015)
This paper deals with the use of controlling in the management of small and medium-sized enterprises in the Czech Republic and its influence on their economic performance. Data from primary research are presented, which determined the extent of implementation of controlling activities in the examined enterprises. The aim of the secondary research was to evaluate the economic performance of enterprises with and without controlling and to determine whether it is possible to confirm the hypothesis of better economic (financial) results of the enterprises that apply controlling in their management process. The two groups of enterprises are compared by using calculated arithmetic means and medians of selected economic indicators. The source of data is the corporate database MagnusWeb. The compared data are also subjected to statistical analysis. Nonparametric tests í. e. the Mann-Whitney U test and the Kolmogorov-Smirnov test to determine statistically significant differences between the financial results of the enterprises that use and do not apply controlling.
Keywords: management; controlling; economic performance; financial analysis; small and medium-sized enterprises; M21